2019
DOI: 10.1007/s00435-019-00464-2
|View full text |Cite
|
Sign up to set email alerts
|

Negative allometric growth during ontogeny in the large pelagic filter-feeding basking shark

Abstract: Many pelagic shark species change body and fin shape isometrically or by positive allometry during ontogeny. But some large apex predators such as the white shark Carcharodon carcharias or the tiger shark Galeocerdo cuvier show distinct negative allometry, especially in traits related to feeding (head) or propulsion (caudal fin). In particular, changes in propulsion are attributed to a shift in swimming mode. The more heterocercal caudal fin of younger individuals with its large caudal fin span seemingly aids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 47 publications
(96 reference statements)
2
30
1
Order By: Relevance
“…The observed growth type seems to confirm that small‐bodied sharks allegedly undergo isometric morphological growth and don't change their body shape during their life, as already observed in previous studies (Ahnelt et al, 2020; Fu et al, 2016; Irschick et al, 2017; Irschick & Hammerschlag, 2015). Other studies provided different b values for the species considered, sometimes suggesting an allometric growth type.…”
Section: Discussionsupporting
confidence: 88%
“…The observed growth type seems to confirm that small‐bodied sharks allegedly undergo isometric morphological growth and don't change their body shape during their life, as already observed in previous studies (Ahnelt et al, 2020; Fu et al, 2016; Irschick et al, 2017; Irschick & Hammerschlag, 2015). Other studies provided different b values for the species considered, sometimes suggesting an allometric growth type.…”
Section: Discussionsupporting
confidence: 88%
“…These discrepancies arise most frequently in the measurements from rostrum tip to second dorsal fin origin, to the pelvic origin, and to the anal fin origin and infrequently in the rostrum tip to first dorsal fin origin as well as in the fin length measurements (Figure 1). Nonetheless, these residuals, on average −0.31% across all species and measurements, are well within the range of proportional measurements from actual specimens, on average 1.61% across all species and measurements (Ahnelt et al, 2020; Cooper et al, 2020; Yano et al, 2007; Data S1). This validates the collated pictographs as representative of actual specimens and bolsters the use of pictographs as morphological trait metrics.…”
Section: Resultssupporting
confidence: 66%
“…The overall trend for growth in pyjama sharks within this study suggested isometric growth for females and negative allometry for males regardless of being captive or wild-caught. Previous studies have suggested that small-bodied sharks that exhibit little movement typically follow an isometric growth pattern (Irschick and Hammerschlag 2015; Ahnelt et al 2020). Allometry in sharks is likely driven by habitat change (Gayford et al 2023), therefore sexual segregation across habitat could be considered as the primary driver for negative allometry in males.…”
Section: Morphometrics and Growthmentioning
confidence: 99%